2019
DOI: 10.1002/chem.201806113
|View full text |Cite
|
Sign up to set email alerts
|

Mass Spectrometric Identification of [4Fe–4S](NO)x Intermediates of Nitric Oxide Sensing by Regulatory Iron–Sulfur Cluster Proteins

Abstract: Nitric oxide (NO) can function as both a cytotoxin and a signalling molecule. In both cases, reaction with iron–sulfur (Fe–S) cluster proteins plays an important role because Fe–S clusters are reactive towards NO and so are a primary site of general NO‐induced damage (toxicity). This sensitivity to nitrosylation is harnessed in the growing group of regulatory proteins that function in sensing of NO via an Fe–S cluster. Although information about the products of cluster nitrosylation is now emerging, detection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(53 citation statements)
references
References 55 publications
1
52
0
Order By: Relevance
“…Interestingly, no nitrosylated forms of the WhiD [4Fe-4S] cluster, nor any iron-nitrosyl products were detected by non-denaturing mass spectrometry. Such species were recently detected by mass spectrometry for ScWhiD (22), suggesting that NO-complexes of SvWhiD are less stable under the conditions of the mass spectrometry experiments than those of ScWhiD.…”
Section: Svwhid [4fe-4s] Cluster Reacts With Nomentioning
confidence: 98%
“…Interestingly, no nitrosylated forms of the WhiD [4Fe-4S] cluster, nor any iron-nitrosyl products were detected by non-denaturing mass spectrometry. Such species were recently detected by mass spectrometry for ScWhiD (22), suggesting that NO-complexes of SvWhiD are less stable under the conditions of the mass spectrometry experiments than those of ScWhiD.…”
Section: Svwhid [4fe-4s] Cluster Reacts With Nomentioning
confidence: 98%
“…For example, Crack et al. first illustrated the application of nMS to study physiologically relevant cluster chemistry . However, use of the application has been limited due to challenges from cluster instability and from the additional sample preparation steps required to spray intact cluster‐bound proteins from mass spectrometric compatible buffers.…”
Section: Figurementioning
confidence: 99%
“…For example, Crack et al first illustrated the application of nMS to study physiologically relevant cluster chemistry. [12][13][14][15][16][17][18][19][20][21][22] However, use of the application has been limited due to challenges from cluster instability and from the additional sample preparation steps required to spray intact cluster-bound proteins from mass spectrometric compatible buffers. The majority of such proteins characterized by mass spectrometry have Fe-S clusters buried inside the protein core and not at the protein-protein interface.…”
mentioning
confidence: 99%
“…While the number of available thiols is unchanged between the anaerobic and aerobic nitrosylation of A. ferroxidans HiPIP, the O 2 could potentially facilitate elimination of the bridging sulfides. Oxidation of the bridging sulfides has been observed in the nitrosylation of other protein-bound [4Fe4S] clusters with the sulfides remaining bound to the protein as persulfide cysteine, 15,35 and indeed Crack et al observed formation of RRE products in the nitrosylation of several [4Fe4S] proteins. 7 We know that thiolate DNIC species can be converted to RRE under oxidising conditions with the thiolate sulfides as targets of oxidation and disulfide as a byproduct.…”
Section: Dalton Transactions Papermentioning
confidence: 99%
“…32 Non-denaturing mass spectrometry and NRVS have been used productively to identify further products of the nitrosylation reactions of [4Fe4S] proteins. 9,10,[14][15][16][33][34][35] We previously reported IR spectroscopy alongside other spectroscopic methods to show that [2Fe2S] Spinach ferredoxin (Fd) reacts with NO in a manner dependent on the redox environment of the reaction. Nitrosylation of this protein under anaerobic conditions yields a mixture of DNIC and RRE, whereas, in the presence of trace O 2 or the thiolate sequestering reagent, iodoacetamide, RRE is formed as the major product.…”
Section: Introductionmentioning
confidence: 99%